2006
DOI: 10.1177/1090198106296768
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Culturally Tailored Educational Video: Changing Breast Cancer–Related Behaviors in Chinese Women

Abstract: This study developed and evaluated a culturally tailored video guided by the health belief model to improve Chinese women's low rate of mammography use. Focus-group discussions and an advisory board meeting guided the video development. A 17-min video, including a soap opera and physician-recommendation segment, was made in Chinese languages. A pretest/posttest pilot was conducted to evaluate the efficacy of the video in changing knowledge, beliefs, and screening intentions among Chinese women (age >or= 40) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 40 publications
1
90
0
Order By: Relevance
“…Kwok and Sullivan (2006b) also pointed out the importance for addressing and integrating culturally specific health beliefs in health promotion interventions that are oriented towards the Chinese migrants. Other consistent outcomes have been reported; Wang et al (2007) found that after viewing a culturally-tailored video, including physician-recommendations, Chinese women's screening intentions significantly increased and they were less likely to subscribe to an Eastern view of health. This result suggests that combining knowledge of both illness belief systems can improve outcomes.…”
Section: Introductionmentioning
confidence: 54%
“…Kwok and Sullivan (2006b) also pointed out the importance for addressing and integrating culturally specific health beliefs in health promotion interventions that are oriented towards the Chinese migrants. Other consistent outcomes have been reported; Wang et al (2007) found that after viewing a culturally-tailored video, including physician-recommendations, Chinese women's screening intentions significantly increased and they were less likely to subscribe to an Eastern view of health. This result suggests that combining knowledge of both illness belief systems can improve outcomes.…”
Section: Introductionmentioning
confidence: 54%
“…Chinese-Canadian communities were among the first of Canada's ethnocultural groups to be offered tailored health promotion information on breast cancer 16,20,39,40 , but whether those initiatives are improving cancer outcomes remains unclear. More detailed data about ethnicity and immigration status would help to inform health policy, to target and tailor ethnoculturally appropriate health promotion initiatives, and to track the resulting clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research shows that Asians have different views and practices in health care than Whites (9). For example, traditional Chinese stress taking care of one's own health over medical checkups (self-care) and believe that illness is a result of personal fate or luck (10,11). Such cultural views are associated with nonadherence to cancer screening in Chinese American women (10,12).…”
Section: Introductionmentioning
confidence: 99%